Books received from publishers (up to 31 December 1996). (Cultural Studies, 1997)
This article presents information about various books received. Some of the books include: "Scientific Knowledge: A Sociological Analysis," by Barry Barnes, David Bloor and John Henry, "Inside the Minstrel Mask: Readings in Nineteenth-Century Blackface Minstrelsy," edited by Annemarie Bean, James V. Hatch and Brooks McNamara, "The Apparitional Lesbian: Female Homosexuality and Modern Culture," by Terry Castle, "The Social Construction of Nature," by Klaus Eder, and "South Africa: Designing New Political Institutions," edited by Faure Murray and Jan-Erik Lane.